Investigation of Polyhenolic Content of Rose Hip (Rosa canina L.) Tea Extracts: A Comparative Study - Zeynep İlbay; Selin Şahin; Ş. İsmail Kirbaşlar (Foods, 2013)
Three different brands of Rose hip (Rosa canina L.) tea were extracted with water, ethanol (EtOH), methanol (MeOH), and aqueous mixtures (50%, v/v) by ultrasound-assisted extraction (UAE) and Soxhlet methods. Total phenolic content was determined according to the Folin-Ciocalteu method. The results were presented by means of the extract yields and total phenolic contents, expressed in gallic acid equivalent (GAE) per g of dried matter (DM). The greatest amount of extract observed in tea samples was obtained by UAE through water with the value of 619.37 ± 0.58 mg/g DM. Regarding the phenolic content, the best result was achieved by the Soxhlet method through 50% MeOH mixture (59.69 ± 0.89 mg GAE/g DM), followed by the UAE method with water (48.59 ± 0.29 mg GAE/g DM).